2021
DOI: 10.1186/s12906-021-03249-7
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of medicinal plants used for urinary tract infections in pastoralist community in Ethiopia

Abstract: Background Medicinal plants have wide medicament application used to prevent and management of many ailments. These plants are used for primary health care in pastoralist communities who are deprived of modern medical care. They possess extensive therapeutics bioactive coupled with varied chemical structures. However, scientific validation of efficacy and safety of plants used to treat the urinary tract infections haven’t been fully exploited. The aim of this study was to evaluate antimicrobial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
(42 reference statements)
2
15
0
Order By: Relevance
“…-The assay of adhesion carried out at the MIC showed a reduction of up to 80% of the adhesion index accompanied with reductions in motility and polyamide production. [36] seed extract tannins, steroids, terpenes, coumarins, flavonoids, andglycosides uropathogens E. coli, Enterococcus faecalis, S. aureus, and K. pneumonia -This study showed urobactericidal activity against different strains that were clinically isolated from patients suffering from urinary tract infections.…”
Section: Mas L-cornelian Cherrymentioning
confidence: 81%
See 3 more Smart Citations
“…-The assay of adhesion carried out at the MIC showed a reduction of up to 80% of the adhesion index accompanied with reductions in motility and polyamide production. [36] seed extract tannins, steroids, terpenes, coumarins, flavonoids, andglycosides uropathogens E. coli, Enterococcus faecalis, S. aureus, and K. pneumonia -This study showed urobactericidal activity against different strains that were clinically isolated from patients suffering from urinary tract infections.…”
Section: Mas L-cornelian Cherrymentioning
confidence: 81%
“…The antimicrobial effects of plant extracts are attributed to multiple mechanisms: directly killing microbes, interfering with microbial adhesion to epithelial cells and biofilm formation, stopping the multiplication of pathogens, restoring dysbiosis, improving the host protection acting on natural barriers, serving as immunomodulators, or boosting body oxidant status [35]. Therefore, using whole plant extracts is recommended, as the biologically active compounds work synergistically and have different mechanisms of action [36]. In the last years, some reports have enlisted botanicals helpful in preventing and curing UTI and made synopses with the therapeutical potential of medicinal plants for the management of UTI [1][2][3][4][5][6][36][37][38][39].…”
Section: Management Of Recurrent Uti By Non-antibiotic Plant-based Pr...mentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of the extracts to inhibit the growth of these organisms in-vitro may be due to the presence of flavonoids which are in both aqueous and ethanol extracts. Flavonoids, terpenoids and cardiac glycoside are known to have antibacterial activities and curative properties against bacterial pathogen (Atanasov et al, 2015;Gadisa et al, 2019;Gadisa and Tadesse, 2021). The plant studied here can be seen as a potential source of useful antimicrobial drugs.…”
Section: Discussionmentioning
confidence: 99%